In vitro and in vivo evaluation of a sublingual fentanyl wafer formulation - Lim SCB; Paech MJ; Sunderl; B; Liu Y (Dove Medical Press, 2013)
Stephen CB Lim,1,3 Michael J Paech,2 Bruce Sunderland,3 Yandi Liu3 1Pharmacy Department, Armadale Health Service, Armadale, 2School of Medicine and Pharmacology, University of Western Australia, and Department of Anaesthesia and Pain Medicine, King Edward Memorial Hospital for Women, Subiaco, 3School of Pharmacy, Curtin Health Innovation Research Institute, Curtin University, Perth, WA, Australia Background: The objective of this study was to prepare a novel fentanyl wafer formulation by a freeze-drying method, and to evaluate its in vitro and in vivo release characteristics, including its bioavailability via the sublingual route. Methods: The wafer formulation was prepared by freeze-drying an aqueous dispersion of fentanyl containing sodium carboxymethylcellulose and amylogum as matrix formers. Uniformity of weight, friability, and dissolution testing of the fentanyl wafer was achieved using standard methods, and the residual moisture content was measured. The fentanyl wafer was also examined using scanning electron microscopy and x-ray diffraction. The absolute bioavailability of the fentanyl wafer was evaluated in 11 opioid-naïve adult female patients using a randomized crossover design. Results: In vitro release showed that almost 90% of the fentanyl dissolved in one minute. In vivo, the first detectable plasma fentanyl concentration was observed after 3.5 minutes and the peak plasma concentration between 61.5 and 67 minutes. The median absolute bioavailability was 53.0%. Conclusion: These results indicate that this wafer has potential as an alternative sublingual fentanyl formulation. Keywords: absolute bioavailability, fentanyl wafer, in vitro dissolution, in vivo study, pharmacokinetics, sublingual